Physical Activity Levels, Sport Activities, and Risk of Acute Myocardial Infarction: Results of the INTERHEART Study in China. (February 2014) - Cheng, Xiaoru; Li, Wei; Guo, Jin; Wang, Yang; Gu, Hongqiu; Teo, Koon; Liu, Lisheng; Yusuf, Salim
Physical activity (PA) during leisure time has been inversely associated with cardiovascular disease risk in the Western populations. We evaluated PA at work and leisure time in relation to acute myocardial infarction (AMI) in Chinese population. We conducted a hospital-based case–control study. The cases had first AMI (n = 2909). The controls (n = 2947) were matched to the cases in age and sex. The odds ratios (ORs) of leisure-time PA for strenuous exercise compared to mainly sedentary was 0.74 (95% confidence interval [CI]: 0.61-0.90) and for moderate exercise it was 0.96 (95% CI: 0.85-1.08). Multivariate adjustment did not substantially alter the association. The ORs of work-related PA for heavy PA compared to mainly sedentary was 1.44 (95% CI: 1.06-1.94), for climbing and lifting was 1.00 (95% CI: 0.77-.30), and for walking was 0.90 (95%CI: 0.75-1.07). Leisure-time PA was protective for AMI risk compared to sedentary lifestyles in a population in China.